PENERAPAN ASAS SEDERHANA, CEPAT, DAN BIAYA RINGAN DALAM PENYELESAIN PERKARA WARIS DI PENGADILAN AGAMA SUNGGUMINASA KELAS 1B - Ahmad Waliyuddin Hasanuddin; Lomba Sultan; Ibnu Izzah (Qadauna: Jurnal Ilmiah Mahasiswa Hukum Keluarga Islam, 2023)
This research discusses the application of simple, fast, and low-cost principles in resolving inheritance cases at the Sungguminasa Class IB Religious Court. This research is a type of field research and qualitative research with an empirical legal approach. The results of the research show that the application of the principles of simplicity, speed, and low cost in inheritance cases at the Sungguminasa Class IB Religious Court has been well implemented, but especially in inheritance cases, it is very difficult to apply the principles of simplicity, speed, and low cost. low cost. There are several factors that hinder the simple, fast, and low-cost principles from being maximized at the Sungguminasa Class IB Religious Court, namely differences in the area of residence of the parties involved in the case, the summoning of the parties, and the use of lawyers. As an implication, for those who bring inheritance cases to the Sungguminasa Class IB Religious Court, especially in the case of the settlement process, to avoid complicating the process, the defendant should know how to proceed. The application of the principle of simple, fast, and short life is possible because our own decision as litigants is to make peace before a judge.